Initial experience with orbital atherectomy in a non-surgical center in Portugal - Faria, Daniel (2024)
Introduction and objectives: Percutaneous coronary intervention (PCI) of severely calcified lesions is associated with a higher risk of procedural complications, suboptimal stent expansion, and in-stent restenosis. Lesion preparation with orbital atherectomy (OA) in severely calcified lesions has been shown to increase procedural success and decrease reintervention rates. In this study, we sought to report the procedural safety and efficacy of our initial experience with OA in a non-surgical center in Portugal. Methods: Patients with severely calcified coronary lesions who were treated with intended intravascular ultrasound (IVUS) guided OA were included in a prospective single-center registry. We evaluated several endpoints, including: debulking success, defined <50% residual stenosis severity after OA; procedural success, defined as stent implantation according to OptimalIVUS PCI criteria; use of additional calcium debulking strategies; and procedural complications, including coronary no-reflow, dissection, perforation or side branch occlusion. Patients were followed up for 30 days to assess early cardiovascular or procedure-related death, myocardial infarction, myocardial injury and reintervention. Results: Between January 2023 and September 2023, 37 patients and 53 coronary arteries underwent OA. IVUS imaging was used in all cases. Debulking and procedural success were achieved in 90.5% and 97.3% of cases, respectively. In 26 (49.1%) lesions, additional calcium debulking techniques were needed. Procedural complications occurred in three cases and one patient died during hospitalization. Conclusion: Our initial experience with OA for heavily calcified coronary lesions demonstrated high procedural success and overall favorable clinical outcomes. (c) 2024 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espana, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/bync-nd/4.0/).